2022
DOI: 10.3389/fpls.2022.866478
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Pathways Involved in Maize Resistance to Fusarium Ear Rot and Kernel Contamination With Fumonisins

Abstract: Fusarium verticillioides is a causal agent of maize ear rot and produces fumonisins, which are mycotoxins that are toxic to animals and humans. In this study, quantitative trait loci (QTLs) and bulk-segregant RNA-seq approaches were used to uncover genomic regions and pathways involved in resistance to Fusarium ear rot (FER) and to fumonisin accumulation in maize kernels. Genomic regions at bins 4.07–4.1, 6–6.01, 6.04–6.05, and 8.05–8.08 were related to FER resistance and/or reduced fumonisin levels in kernels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 109 publications
(146 reference statements)
2
18
0
Order By: Relevance
“…(2015) observed strong correlations (r = 0.97) between disease severity and FUM. Similarly, Cao et al. (2022) found strong genotypic correlation (r g = 0.85) between FUM and FER severity after kernel inoculation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…(2015) observed strong correlations (r = 0.97) between disease severity and FUM. Similarly, Cao et al. (2022) found strong genotypic correlation (r g = 0.85) between FUM and FER severity after kernel inoculation.…”
Section: Discussionmentioning
confidence: 73%
“…For FER, Butrón et al (2015) observed strong correlations (r = 0.97) between disease severity and FUM. Similarly, Cao et al (2022) found strong genotypic correlation (r g = 0.85) between FUM and FER severity after kernel inoculation. Based on this, selection for FER-resistant lines would indirectly reduce fumonisins accumulation (Maschietto et al, 2017;Galićet al, 2019).…”
Section: Figurementioning
confidence: 73%
“…Eight RILs of maize were selected from a set of 144 RILs derived from the cross between the European flint inbred line EP42 (susceptible to FER and kernel contamination with fumonisins) and the American dent inbred line A637 (resistant), and previously genotyped and phenotyped for FER and kernel fumonisin content under inoculation with F. verticillioides ( Santiago et al, 2013 ; Samayoa et al, 2014 ; Cao et al, 2022 ). The four RILs with the lowest values (resistant) for fumonisin content (10-15 µg/g) and FER (~ 2 in a visual scale from 1 to 7) along with the four RILs with the highest values (susceptible) for fumonisin content (55-75 µg/g) and FER (~ 4) were selected based on previous evaluations ( Supplementary Table 1 ) ( Cao et al., 2022 ). In 2018, 15 seeds from each RIL were sown in a single row of 3.5 m; distance between adjacent rows being 0.8 m. RILs were arranged in four pairs, each pair formed with one resistant and one susceptible RIL.…”
Section: Methodsmentioning
confidence: 99%
“…RILs within each pair were planted in adjacent rows in order to minimize the contribution of field heterogeneity to differential metabolite content between resistant and susceptible inbreds. We self-crossed at least six plants per RIL, and 15 days later the main ear of each plant was inoculated, using a kernel inoculation technique ( Cao et al., 2014 ), with a spore suspension of F. verticillioides as previously described ( Cao et al, 2022 ). Ears were individually collected at 3 or 10 days after inoculation treatment (dat) (18 and 25 days after pollination, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation